Software para la Gestión de Proyectos ágiles de TI tipo SCRUM (2020)
The emerging needs accompanied by the dynamism of the world have required tasks that as human beings we must respond to. The projects then arise as a response to the needs of society and have an objective, to provide solutions to these established problems. According to the PMI "the project management processes are divided into five groups: Start, Planning, Execution, Monitoring and Control and Closure" (Us and PMI, 2020), each of these stages can be influenced by risks and require good administration. Currently in the IT area, the different methodologies for project management are widely used, however many of the strategies and methodologies are conceptual and their application can be very tedious for professionals in project management. The most widely used methodology is SCRUM, which is “an iterative and incremental framework for the development of projects, products and applications. Structure the development in work cycles called Sprints ”. (Deemer, P., Benefield, G., Larman, C., & Vodde, B. 2009). To solve this need was constructed a software that supports project management under the agile scrum methodology that allows you to administer, plan, coordinate, monitor and control all the activities and resources of a project. For this, a literature review was carried out that helped us clarify important concepts in relation to project management, their importance, the associated risks and their mitigation, and later a web application and a mobile application were developed that allows professionals in the IT área to administer, plan, coordinate, monitor and control all the activities and resources of a project